Legal Education on Land Rights and the Prevention of Land Disputes for Rural Communities - Rini T Simangunsong; Motlan Gultom; Oktavia Purnamasari Sigalingging; Parlian Simamora; Vhebriyanti Hutagaol (Yayasan Rahmat Islamiyah, 2026)
Legal literacy on land rights remains important for rural communities because land has economic, social, and family value. Many land disputes begin from weak administrative awareness, unclear boundaries, informal transfers, inheritance issues, and limited knowledge of land registration procedures. This community service article describes legal counseling on land rights and prevention of land disputes for rural communities. The activity was designed as participatory legal education in Desa/Kelurahan Siaro, Kecamatan Siborongborong, Kabupaten Tapanuli Utara. The method consisted of preliminary coordination, preparation of legal counseling materials, delivery of key concepts, case-based discussion, question and answer session, and qualitative evaluation of participants responses. The counseling materials covered types of land rights, land registration, certificates as strong evidence, prudent land transactions, inheritance-related land problems, and peaceful dispute settlement. The results show that legal counseling helped participants understand the difference between physical control and legally recognized evidence of rights. Participants also became more aware of the need to check documents, clarify boundaries, involve rightful family members, and use deliberation or mediation before disputes escalate. The activity confirms that community-based legal education can strengthen preventive legal culture in rural land administration.